The American-Turkish Political Relations 1991-2001 A.D. - et. al., Ahmed Mahmood Alaw Al-Samarrae , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The U.S. Turkish relations are one of the issues of interest to the researcher in the field of politics as it is a relationship between two important and active parties in the international arena, especially the Middle East region. The United States had a great interest in Turkey's siding with the West. Turkey also found its interest in that, so we found it a member of the NATO. In contrast to the expected after the collapse of the Soviet Union in 1991, Turkey's importance in the strategic perception of the United States did not end, especially since Turkey's geographical proximity seemed to be more strained and changing, not to mention the Western model adopted by Turkey, which the United States wants to be an example in the region. The American- Turkish relations for the period (1991-2001) were influenced by radical and fundamental changes. These variables are either internal or international. The internal factors influencing this relationship lie in the Turkish political parties which play a major role in the political process. The other factor is the Kurdish issue, which Turkey is dealing with very cautiously, while the United States has used it as a pressure card on the Turkish governments. It has not pursued a consistent policy on the issue and has always appeared against human rights violations. The other external factors, including the Cyprus issue, are a source of concern for the alliance strategy between the two countries from the 1960s until the present, and there is the matter of dealing with terrorism especially after the events of 11 September 2001. The other factor is the question of the EU accession which is the Turkish dream and the source of interest for its foreign policy. Which the United States is trying to show that it is the only one who able to persuade the Europeans to accept the membership of Turkey. Turkut Ouzel's government has sought to play a pivotal role at the regional and global levels and in the realization of Turkish interests in the Central Asian republics, the Black Sea basin, the Mediterranean basin, the Middle East region, the Arab neighbors, Israel, Iran and the Balkans, beside achieving the economic development and self-sufficiency; efforts are incessant to fulfill those ambitions. Turkey has acted to change the unilateral approach towards the United States and the NATO to another one that includes multilateral policies related to the normalization of relations with the African and Asian worlds as well as neighboring countries.